2022
DOI: 10.1088/2053-1591/ac7513
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of electronic and optical behavior of the interface of Co2FeAl/AlN heusler alloy

Abstract: Based on the density functional theory, the electronic, optical, and structural properties of the Co2FeAl/AlN Interface have been studied. It is shown that the Co2FeAl compound is a half-metal with 100% spin polarization at the Fermi level, and the growth of this compound on the AlN semiconductor changes its stability. The best interface connection from the point of view of stability occurs in the Co-Co-Al case, which has a semi-metallic and spin polarization of the interface, which candidate it for spintronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…The lattice constant of semi-metallic Ir 2 CrSi exhibits 100% spin polarization at the Fermi level, while Ir 2 CrGe has 99% spin polarization at the Fermi level, making these alloys suitable for spintronic devices. Lahoupour et al 12 investigated the Co 2 FeAl/AlN using DFT methods. Studies of the composition of Co 2 FeAl showed that it is a semi-metal that has 100% polarization at the Fermi level.…”
Section: Introductionmentioning
confidence: 99%
“…The lattice constant of semi-metallic Ir 2 CrSi exhibits 100% spin polarization at the Fermi level, while Ir 2 CrGe has 99% spin polarization at the Fermi level, making these alloys suitable for spintronic devices. Lahoupour et al 12 investigated the Co 2 FeAl/AlN using DFT methods. Studies of the composition of Co 2 FeAl showed that it is a semi-metal that has 100% polarization at the Fermi level.…”
Section: Introductionmentioning
confidence: 99%